PENERAPAN BERMAIN BILANGAN MELALUI APLIKASI EDUGAME MARU USIA 4-5 TAHUN - Hudaifah, Hudaifah; Maharani, Fany Depita; Rahma, Eyda; Widjayatri, Rr. Deni (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2023)
The purpose of this study was to determine the application of playing numbers through the EduGame Maru application in early childhood 4-5 years. This study uses a participatory qualitative method using an observation model. This study uses data collected through observations and interviews at Al-Quran Al-Maghfiroh Kindergarten with a total of 3 children. From the results of research, the application of playing numbers through the EduGame Maru application can improve children's ability to mention the sequence of numbers 0-9, children recognize concepts and symbols of numbers 0-9, children are able to recognize number problems 0-9, children are able to compare objects from the most and little, able to match numbers that are missing from the sequence, and children are able to obey the rules of the educational game EduGame Maru.